2020
DOI: 10.3352/jeehp.2020.17.4
|View full text |Cite
|
Sign up to set email alerts
|

Moroccan residents’ perceptions of the hospital learning environment measured with the French version of the Postgraduate Hospital Educational Environment Measure

Abstract: Purpose: This study aimed to assess the educational environment of residents in Morocco and to compare residents’ perceptions depending on their specialty.Methods: We applied the French version of the Postgraduate Hospital Educational Environment Measure (PHEEM) to measure the educational environment at 6 hospitals in Rabat from January to June 2017. The internal reliability of the questionnaire was assessed using Cronbach’s α coefficient. Principal component analysis was conducted to assess the construct vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
1
5
0
2
Order By: Relevance
“…The average PHEEM score in our study was higher than previous studies [29,57] indicating more positive views about the learning environment in our study, and this finding was similar to others from South Africa, Saudi Arabia and Morocco [58][59][60]. Almost half of the residents (46.3%) found their educational environment to be more positive than negative, and 40.9% found it more negative than positive.…”
Section: Discussionsupporting
confidence: 85%
“…The average PHEEM score in our study was higher than previous studies [29,57] indicating more positive views about the learning environment in our study, and this finding was similar to others from South Africa, Saudi Arabia and Morocco [58][59][60]. Almost half of the residents (46.3%) found their educational environment to be more positive than negative, and 40.9% found it more negative than positive.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, an item overlapped between components 1 and 2. Interestingly, Berrani et al found similar results, including a 3-or 4-dimensional construct, with a predominant component having 30% variance and encompassing 17 items (31). Both findings are in agreement, suggesting that the PHEEM construct should be revised to adapt to a particular population's cultural characteristics, which may affect the understanding and interpretation of the items.…”
Section: Validity Of the Post-graduate Hospital Educational Environme...mentioning
confidence: 74%
“…However, these relationships were significantly stronger with the autonomy dimension of PHEEM (29). Other reports of PHEEM scores from a study conducted in the United Kingdom, Morocco, and Iran also highlight the regional disparity in perception of the clinical learning environment (25,30,31). However, whether the PHEEM tool enables reliable international and cross-cultural comparability is unclear; hence, comparing the scores should be interpreted cautiously outside a given setting.…”
Section: Assessing the Clinical Learning Environmentmentioning
confidence: 99%
“…In modern education, the essence of the concept of "educational environment" and its various aspects were studied by Aars and Christensen [9], Abed et al [10], Alahmadi [11], Al-Maroof et al [12], Andersson [13], Berrani et al [14], Bondarenko et al [15], Camacho et al [16], Chrysafiadi et al [17], Dotsenko [18], Fuentes-Moreno et al [19], Horbatiuk et al [20], Huh [21], Kerimbayev et al [22], Kyslova et al [23], Lechthaler et al [24], Lawless and Riel [25], Lee et al [26], Morze and Kucherovska [27], Mousavi et al [28], Orlando et al [29], Sahu et al [30], Shapovalov et al [31], Smogorzewska et al [32], Stratulat et al [33], Tleubay et al [34], Uchitel et al [35], Yang et al [36] and others. The educational environment is considered as a factor of education from the standpoint of understanding education as a special sphere of social life.…”
Section: Related Workmentioning
confidence: 99%